Implications and Mechanisms of Antiviral Effects of Lactic Acid Bacteria: A Systematic Review - Farahmandi, Fargol; Parhizgar, Parynaz; Mozafari Komesh Tape, Parya; Bizhannia, Fahimeh; Rohani, Fateme Sadat; Bizhanzadeh, Marzieh; Mostafavi Alhosseini, Zeinab Sadat; Hosseinzade, Maede; Farsi, Yeganeh; Nasiri, Mohammad Javad (International Journal of Microbiology, 2023)
Background. Lactic acid bacteria (LAB) are among the most important strains of probiotics. Some are normal flora of human mucous membranes in the gastrointestinal system, skin, urinary tract, and genitalia. There is evidence suggesting that LAB has an antiviral effect on viral infections. However, these studies are still controversial; a systematic review was conducted to evaluate the antiviral effects of LAB on viral infections. Methods. The systematic search was conducted until the end of December 17, 2022, using international databases such as Scopus, Web of Science, and Medline (via PubMed). The keywords of our search were lactic acid bacteria, Lactobacillales, Lactobacillus (as well as its species), probiotics, antiviral, inhibitory effect, and virus. Results. Of 15.408 potentially relevant articles obtained, 45 eligible in-vivo human studies were selected for inclusion in the study from databases, registers, and citation searching. We conducted a systematic review of the antiviral effects of the LAB based on the included articles. The most commonly investigated lactobacillus specie were Lactobacillus rhamnosus GG and Lactobacillus casei. Conclusion. Our study indicates that 40 of the selected 45 of the included articles support the positive effect of LAB on viral infections, although some studies showed no significant positive effect of LABs on some viral infections.